Fast three-color single-molecule FRET using statistical inference - Janghyun Yoo (Nature Portfolio, 2020)
Three-colour FRET is a powerful tool to study macromolecular conformational dynamics, but is temporally limited due to the experimental complexity. Here the authors develop experimental and analytical methods for probing submillisecond-time scale dynamics using single continuous-wave excitation.